2019
DOI: 10.3389/fbioe.2019.00303
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy: Guiding Light for the Extracellular Matrix

Abstract: The extracellular matrix (ECM) consists of a complex mesh of proteins, glycoproteins, and glycosaminoglycans, and is essential for maintaining the integrity and function of biological tissues. Imaging and biomolecular characterization of the ECM is critical for understanding disease onset and for the development of novel, disease-modifying therapeutics. Recently, there has been a growing interest in the use of Raman spectroscopy to characterize the ECM. Raman spectroscopy is a label-free vibrational technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 136 publications
(154 reference statements)
0
98
0
2
Order By: Relevance
“…Since it has been shown that fascicles and interfascicular matrix have different proteomic profiles and demonstrate different age-related changes [43], differences in the Raman spectra can be expected. Future studies could use Raman spectroscopy to interrogate cells directly [12,14,15] and perform label-free classification of different cell populations in fascicles and the IFM, overcoming some of the current technological difficulties in studying tendon sub-structure composition.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown that fascicles and interfascicular matrix have different proteomic profiles and demonstrate different age-related changes [43], differences in the Raman spectra can be expected. Future studies could use Raman spectroscopy to interrogate cells directly [12,14,15] and perform label-free classification of different cell populations in fascicles and the IFM, overcoming some of the current technological difficulties in studying tendon sub-structure composition.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, quantitative phase imaging (QPI) has been used to investigate morphology of live cells and identify disease-specific cellular phenotypes [12][13][14][15][16][17][18][19][20][21][22]. On the other hand, Raman spectroscopy has been employed to measure the biomolecular composition with single cell resolution for cell differentiation and disease identification [23][24][25][26][27][28][29][30][31][32]. Since both the molecular and morphological changes are associated with malignant transformations, we have sought to develop a morphomolecular microscopy (3M) platform, which combines the complementary morphological and biochemical information content into diagnostic frameworks [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has become one of the key analytical technologies in life sciences or biomedicine enabling a label-free detection of the molecular composition of complex samples such as cells and tissues with little or no sample preparation [1][2][3][4]. In combination with microscopy-based imaging, a spatial resolution between 300 and 500 nm can be achieved, which allows for subcellular resolution, for example, imaging the nucleus and lipid droplets inside a single cell [5,6].…”
Section: Introductionmentioning
confidence: 99%